Microalgae as next generation plant growth additives: Functions, applications, challenges and circular bioeconomy based solutions - Parmar, Priyanka; Kumar, Raman; Neha, Yograj; Srivatsan, Vidyashankar (Frontiers in Plant Science, 2023)
Sustainable agriculture practices involve the application of environment-friendly plant growth promoters and additives that do not negatively impact the health of the ecosystem. Stringent regulatory frameworks restricting the use of synthetic agrochemicals and the increase in demand for organically grown crops have paved the way for the development of novel bio-based plant growth promoters. In this context, microalgae biomass and derived agrochemicals offer novel sources of plant growth promotors that enhance crop productivity and impart disease resistance. These beneficial effects could be attributed to the presence of wide range of biomolecules such as soluble amino acid (AA), micronutrients, polysaccharides, phytohormones and other signaling molecules in microalgae biomass. In addition, their phototrophic nature, high photosynthetic efficiency, and wide environmental adaptability make them an attractive source of biostimulants, biofertilizers and biopesticides. The present review aims to describe the various plant growth promoting metabolites produced by microalgae and their effects on plant growth and productivity. Further, the effects elicited by microalgae biostimulants with respect to different modes of applications such as seed treatments, foliar spray and soil/root drenching is reviewed in detail. In addition, the ability of microalgae metabolites to impart tolerance against various abiotic and biotic stressors along with the mechanism of action is discussed in this paper. Although the use of microalgae based biofertilizers and biostimulants is gaining popularity, the high nutrient and water requirements and energy intensive downstream processes makes microalgae based technology commercially unsustainable. Addressing this challenge, we propose a circular economy model of microalgae mediated bioremediation coupled with biorefinery approaches of generating high value metabolites along with biofertilizer applications. We discuss and review new trends in enhancing the sustainability of microalgae biomass production by co-cultivation of algae with hydroponics and utilization of agriculture effluents.